Specification for electromechanical components for electronic equipment: basic testing procedures and measuring methods. Cable-clamping tests, explosion hazard tests, chemical resistance tests, fire hazard tests, r.f. resistance tests, capacitance tests, shielding and filtering tests and magnetic interference tests Part 9, (30th November 1979) - British Standards Institution,
No abstract available